Perceptions of Vocabulary Teaching Methods Among EFL Teachers - Bouirane, Ahlam (المدرسة العليا للأساتذة آسيا جبار قسنطينة, 2016)
This paper investigates the perceptions of teachers of English as a foreign language towards vocabulary teaching. The participants are three oral expression teachers and 32 teachers at the English Language and Literature Department at Mohamed Lamine Dabaghine University. The research follows a quantitative and a qualitative design that uses a questionnaire and an observation respectively. The questionnaire collected the perceptions of the 32 participants towards their vocabulary teaching methods. The observation collected concrete classroom vocabulary teaching data that were compared to the observed teachers’ questionnaire responses. Analysis of the questionnaire data revealed different perceptions of vocabulary teaching methods. Moreover, analysis of the observation data along with the observed teachers’ responses to the questionnaire confirmed explicit teaching of vocabulary using the presentation-practice-production stages.
يتناول البحث طرائق تدريس مفردات اللغة الإنجليزية كلغة أجنبية، وبالتحديد مدى إدراك الأساتذة لمناهج تعليم المفردات، وتتمثل عينة البحث في ثلاثة أستاذة لمادة التعبير الشفوي كمادة تعني بتعليم المفردات، واثنين وثلاثين (32) أستاذا لمواد مختلفة بقسم اللغة والأدب الإنجليزيين بجامعة محمد لمين دباغين سطيف 2. وتجسيدا لأهداف البحث، فقد تم اعتماد المنهج الاستقصائي لجمع المعطيات باستخدام الملاحظة والاستبيان، بينما استخدم الاستبيان لاستقصاء كيفية إدراك الأساتذة لمناهج تعليم المفردات، كما استخدمت الملاحظة لتأكيد نتائج الاستبيان. وبتحليل النتائج المتحصل عليها من الاستبيان تبين أن إدراك الأساتذة لطرائق تعليم المفردات ضعيف، كما بينت نتائج الملاحظة إدراكا ضعيفا وقلة وعي بخصوص مختلف المنهجيات المعتمدة في تدريس المفردات لدى أساتذة التعبير.
Keywords: اللغة الإنجليزية كلغة أجنبية -- تدريس اللغة الإنجليزية -- طرق التدريس